Molecular differences in skeletal muscle after 1 week of active vs. passive recovery from high-volume resistance training - Vann, C. G.; Haun, C. T.; Osburn, S. C.; Romero, M. A.; Roberson, P. A.; Mumford, P. W.; Mobley, C. B.; Holmes, H. M.; Fox, C. D.; Young, K. C.; Roberts, M. D. (The Journal of Strength and Conditioning Research, 2021)
Numerous studies have evaluated how deloading after resistance training (RT) affects strength and power outcomes. However, the molecular adaptations that occur after deload periods remain understudied. Trained, college-aged men (n = 30) performed 6 weeks of whole-body RT starting at 10 sets of 10 repetitions per exercise per week and finishing at 32 sets of 10 repetitions per exercise per week. After this period, subjects performed either active (AR; n = 16) or passive recovery (PR; n = 14) for 1 week where AR completed ~15% of the week 6 training volume and PR ceased training. Variables related to body composition and recovery examined before RT (PRE), after 6 weeks of RT (POST), and after the 1-week recovery period (DL). Vastus lateralis (VL) muscle biopsies and blood samples were collected at each timepoint, and various biochemical and histological assays were performed. Group × time interactions (p < 0.05) existed for skeletal muscle myosin heavy chain (MHC)-IIa mRNA (AR > PR at POST and DL) and 20S proteasome activity (post-hoc tests revealed no significance in groups over time). Time effects (P < 0.05) existed for total mood disturbance and serum creatine kinase and mechano growth factor mRNA (POST > PRE &D L), VL pressure to pain threshold and MHC-IIx mRNA (PRE&DL > POST), Atrogin-1 and MuRF-1 mRNA (PRE < POST < DL), MHC-I mRNA (PRE < POST & DL), myostatin mRNA (PRE & POST < DL), and mechanistic target of rapamycin (PRE > POST & DL). No interactions or time effects were observed for barbell squat velocity, various hormones, histological metrics, polyubiquitinated proteins, or phosphorylated/pan protein levels of 4E-BP1, p70S6k, and AMPK. One week of AR after a high-volume training block instigates marginal molecular differences in skeletal muscle relative to PR. From a practical standpoint, however, both paradigms elicited largely similar responses.